Dietary supplementation with casein/cyanidin-3-O-glucoside nanoparticles alters the gut microbiota in high-fat fed C57BL/6 mice. (30th June 2023) - Lyu, Qiyan; Deng, Hongting; Wang, Shunxin; El-Seedi, Hesham; Cao, Hui; Chen, Lei; Teng, Hui
Highlights: Casein/cyanidin-3-O-glucoside nanoparticles (Cs-C3G) are prepared. Cs-C3G can inhibit the fat accumulation in vivo. Cs-C3G can inhibit oxidative stress in HFD mice. Cs-C3G can restore the abundance and diversity of gut microbiota. Abstract: This study aims to investigate the dietary intervention effect of casein/cyanidin-3-O-glucoside nanoparticles (Cs-C3G) on high-fat-diet (HFD)induced gut microbiota disorders. In HFD-fed C57BL/6mice, Cs-C3G has ameliorated HFD-caused fat accumulation and liver oxidative stress. Cs-C3G as a dietary supplementation can restore the abundance and diversity of gut microbiota with descending the ratio of Firmicutes to Bacteroidetes, increasing some beneficial microorganisms, and reducing some opportunistic pathogenic bacteria. In general, Cs-C3G has a effect on regulating the disturbance of gut microbiota, and then prevents HFD-induced obesity and liver damage.